PHYSICAL, CHEMICAL AND ORGANOLEPTIC PROPERTIES OF SAPODILLA (Achras zapota L.) JAM BASED ON PECTIN AND SUCROSE ADDITION - Yogi Harto; Yessy Rosalina; Laili Susanti (BPFP Faperta UNIB, 2016)
This study was carried out to investigate the effect of sucrose and pectin on physical, chemical and organoleptic properties of sapodilla jam and to determine the best treatment in accordance with SNI. The evaluation consisted of a 2 X 3 factorial design with three replicates, two Pectin concentrations (0.5%, 0.7%) and three sugar concentrations (35%, 45%, 55%). Experimental data were subjected to ANOVA test followed by Tukey's test 5%. The results showed the proportion of pectin and sugar have significantly different impact on color, aroma, taste, a smear of jam and overall consumers acceptance on sapodilla jam. Results of chemical analysis and physical use of pectin have significantly different impact on total dissolved solids (TDS), but has no effect on pH and a smear of jam. The use of sugar affect the TDS and a smear of jam but pH did not differsignificantly. The interaction between pectin and sugar have significantly different impact on a smear of jam but has no effect on pH and TDS. The best product is the use of pectin 0.5% and sugar 55% , brownish-red color (4.20), sweet taste (4,07). aroma is quite flavorful distinctive sapodilla fruit (2.83), smooth texture and easily applied evenly (4.57). The overall consumers acceptance score (4.57). TDS (94.77%), pH (4.4) and fruit fiber positive (+).